Fluorescent cationic probes of mitochondria. Metrics and mechanism of interaction. - Bunting, J R (1989)
Mitochondria strongly accumulate amphiphilic cations. We report here a study of the association of respiring rat liver mitochondria with several fluorescent cationic dyes from differing structural classes. Using gravimetric and fluorometric analysis of dye partition, we find that dyes and mitochondria interact in three ways: (a) uptake with fluorescence quenching, (b) uptake without change in fluorescence intensity, and (c) lack of uptake. For dyes that quench upon uptake, the extent of quenching correlates with the degree of aggregation of the dye to dimers, as predicted by theory (Tomov, T.C. 1986. J. Biochem. Biophys. Methods. 13:29-38). Also predicted is the relationship observed between quenching and the mitochondria concentration when constant dye is titrated with mitochondria. Not predicted is the relationship observed between quenching and dye concentration when constant mitochondria are titrated with dye. Because a limit to dye uptake exists, in this case, the degree of quenching decreases as dye is added. A Langmuir isotherm analysis gives phenomenological parameters that predict quenching when it is observed as a function of dye concentration. By allowing for a decrease in membrane potential, caused by incorporation of cationic dye into the lipid bilayer, a modification of the Tomov theory predicts the dye titration data. We present a model of cationic dye-mitochondria interaction and discuss the use of these as probes of mitochondrial membrane potential.